Analisis Peran ALMA dalam Meningkatkan Kinerja Keuangan Perbankan di Indonesia dalam Perspektif Teologis - Julius Andhika Prasetyo; Nasirwan (HATTA : Jurnal Pendidikan Ekonomi dan Ilmu Ekonomi, 2026)
Background: The banking sector plays a crucial role in the economy as a financial intermediary, requiring effective and efficient financial management. One important aspect of this management is asset and liability management, which functions to maintain financial balance and control risks. Purpose: This study aims to analyze the role of asset and liability management in the financial performance of banking institutions in Indonesia. Method: The method used was a qualitative descriptive approach based on a literature review, utilizing secondary data sourced from official publications of the Badan Pusat Statistik, Otoritas Jasa Keuangan, academic articles, relevant books, Quran, and Bible. Findings: Research findings indicate that asset and liability management plays a crucial role in managing liquidity and market risk, maintaining financial stability, and enhancing banking profitability. However, the effectiveness of its implementation depends heavily on the quality of management and the policies in place, this is in line with Qs. An-Nisa’:58 and Luke 16:10, which emphasize diligence and responsibility in financial management and several other verses. Conclusions: Asset and liability management is a crucial strategy for improving financial performance and ensuring the sustainability of the banking sector in Indonesia.